Technology change priorities influencing competition quality promotion: Case study of Iran Keaton Polyester Manufacturing Company - Pouria Nour; Behrooz Jamali; Ehsan Ghasemi (Management Science Letters, 2012)
In the changing world with various customers’ demands the businesses tend to improve their advantages to beat their rivals by means of better quality, lower prices and so. For Iranian polyester market quality is of crucial importance and is achieved through changing and updating technologies. According to highly regarded model of CAPTECH, which is recommended by UNIDO, technology parameters are defined in each phase and not generally as a whole. In the end the biggest gaps are defined. The main goal is to prioritize the main parameters affecting Iranian polyester company's quality. In order to fulfill our goal, 20 high and medium managers were questioned for this paper. The questions were gathered according to UNIDO samples. After a qualitative and quantitative test we concluded that the biggest gap is for supply chain(56.91) and the lowest gap is for combination phase(43.97).